E-Welfare Perspective on Social Security: Roles and Challenges of Mobile JKN in Healthcare Access - Gisya Khayla Azanis; Zelfanya Rahmayantari; Nasywa Nurul Aini; Nova Sabrina; Fatkhuri; Reja (JESS (Journal of Educational Social Studies), 2026)
The digitalization of public services has become a key strategy for improving the accessibility and efficiency of healthcare delivery in Indonesia. As part of this transformation, BPJS Kesehatan introduced the Mobile JKN application to simplify administrative processes and expand public access to National Health Insurance (JKN) services. Although previous studies have primarily focused on its effectiveness and user satisfaction, limited attention has been given to its role within the broader e-welfare framework.This study aims to examine the role of the Mobile JKN application in improving public access to healthcare services from an e-welfare perspective. The study employs a qualitative literature review using the Information Systems Success Model by DeLone and McLean and the Technology Acceptance Model (TAM) by Davis as analytical frameworks. The novelty of this study lies in integrating these two models with the concept of e-welfare to provide a more comprehensive understanding of Mobile JKN as both a digital healthcare service innovation and a digital welfare instrument. The findings indicate that Mobile JKN simplifies administrative procedures, improves time efficiency, and provides integrated healthcare information through a single digital platform. However, several barriers continue to limit the optimal use of Mobile JKN, particularly disparities in digital access, inadequate digital literacy, limited internet and device availability, and technical and data synchronization issues across healthcare facilities. These findings highlight that advancing digital healthcare services involves more than improving technology alone; it also requires stronger institutional capacity, better digital infrastructure, and greater user preparedness to ensure equitable access to healthcare.